Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let's assume there are two players in a dice game; zombie and hero.

The Zombie rolls z fair 6-sided dice.

The Hero rolles h fair 6-sided dice.

If the heroes greatest dice roll is larger than the zombie's greatest dice roll, the hero wins. Otherwise, the zombie wins.

How can I calculate the probability of the hero winning as a function of z and h (without just enumerating the answers).

Example 1: z = 1, h = 2

Zombie rolls (4), hero rolls (1,5). Hero has a higher dice roll and wins.

Example 2: z = 2, h = 2

Zombie rolls (4,4), hero rolls (1,4). Hero does not have a higher dice roll and loses.

Related Question: Given a die, what is the probability that the second roll of a die will be less than the first roll?

share|improve this question

1 Answer 1

up vote 4 down vote accepted

Let $Z$ denote the greatest dice roll of Zombie and $H$ the greatest dice roll of Hero. Assume Zombie's rolls and Hero's rolls are independent

Then $\mathrm P(Z\leqslant n)=(n/6)^z$ for every $1\leqslant n\leqslant 6$ hence $\mathrm P(Z= n)=(n/6)^z-((n-1)/6)^z$. Likewise, $\mathrm P(H\leqslant n)=(n/6)^h$ hence $\mathrm P(H\gt n)=1-(n/6)^h$ for every $1\leqslant n\leqslant 6$. This yields $$ \mathrm P(H\gt Z)=\sum_{n=1}^6\mathrm P(Z=n)\mathrm P(H\gt n)=\sum_{n=1}^6((n/6)^z-((n-1)/6)^z(1-(n/6)^h), $$ that is, $$ \mathrm P(H\gt Z)=1-\frac1{6^{z+h}}\sum_{n=1}^6(n^z-(n-1)^z)n^h. $$

share|improve this answer
    
The RHS of your final equation should begin with $1$, not $6^{−h}$. –  Byron Schmuland Jan 25 '12 at 16:16
    
@Byron: Indeed it should. Thanks. –  Did Jan 25 '12 at 16:38

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.